BIPV market growth: SWOT Analysis and favorable factors - Kumar, Nallapaneni Manoj; Sudhakar, K.; Samykano, Mahendran; Jayaseelan, V. (IEEE, 2018)
Building integrated photovoltaics is an advanced and newly emerged technology in the photovoltaic industry focusing on the application of power generation as well as the building infrastructure. In recent years PV systems have seen huge market potentials, and these are depended on various factors. Like PV systems, the market growth for BIPV is also influenced by various factors. In this paper, an analysis is carried out on such factors that leads to the BIPV market expansions. Primarily, SWOT (Strength, Weakness, Opportunity, and Threat) analysis of BIPV is analyzed in general way. Secondly, all the favorable factors were grouped and classified under six categories. These factors include the Energy, Sustainable Built Environment, Architecture & Design, Material & Civil Structure, Economic Gains, and Safety & Security. Finally, these factors were clearly discussed, and conclusions were made which would help in the BIPV growth.